Characterization of fish assemblages according to trophic level and connectivity of gravel pit lakes from Ile de France region - Montagne, Sebastien (2012)
Relationships between fish assemblages and environmental characteristics of water bodies are increasingly studied. Fish are a good bioindicator when it comes to evaluating and understanding the ecological status and functioning of lakes. The investigations carried out on the subject are quite recent and some types of lakes have not or have been insufficiently studied. The following is an analysis of fish communities, based on environmental variables from 21 gravel pit lakes, most of which are small (<20ha) and shallow. The use of multivariate statistical analyses, based on fish abundances obtained by standardized protocol and on quantitative environmental data, has generated encouraging results. Two fish assemblages have been identified and are responsive to different trophic levels of these lakes. The assemblage composed of perch (Perca fluviatilis), pumpkinseed (Lepomis gibbosus), pike (Esox lucius) and rudd (Scardinius erythrophtalmus), is dominant in lakes less loaded with organic matter, while the assemblage composed by zander (Sander Lucioperca), bream (Abramis brama and Blicca bjoerkna), ruffe (Gymnocephalus cernuus), and roach (Rutilus rutilus) is characteristic for lakes with a high trophic level. We have then used a comparative approach, highlighting the evolution of four fish descriptors according to different trophic levels and/or different lakes connectivities. These results appear to be significant clues which will allow a better approach in what the research continuity on this subject is concerned, because they helped to raise new thinking ways. In addition to descriptive studies, functional studies could supply new answers to the assessment of the ecological potential and to the management of these lakes